Application of Mobile Electronic Center Mall In Jakarta - Aprianus Rofiq; Hariyanto ,S. Kom, MMSI (Jurnal Sistem Informasi, 2007)
Progressively expanding world of information technology so that all problems can be solvedwith one computer with a design "Mobile Application Mall", with the making of thisapplication is expected to facilitate the people of Jakarta especially in electronic trading onthe Jakarta Center. So that it can save time and make it easier to find information.